Political Clientelism, Political Culture and Development in Africa - Alhassan, Oluwaseun Ige (Kervan, 2019)
Culture, society and development are the three most pertinent factors associated with every human civilization; however, they are distinctive and relative. Thus, development exists distinctively in every society. Today, globalization has promoted and consolidated democracy – ‘liberal democracy’ – almost across the globe as the single ideology and the best form of government that must be practised for the protection of individuals’ fundamental human rights. However, the adoption of liberal democracy varies and continues to create a dichotomous marginality between the ‘capitalist West’ and the so-called developing nations with respect to its results. The pertinent questions are: what is the relevance of liberal democracy to Third World development? How important are the desirability, feasibility, conditions and possibilities of liberal democracy for a country where democracy is alien to its political culture? And how is the cultural and historical backdrop of the developing world different from that of the West? We will explore the importance of political clientelism in African political development and look beyond liberal democracy for an African-like democracy. This essay aims to contribute to our collaborative intellectual efforts by looking at the existence of development in human cultural patterns, the historical perspective of liberal democracy, its meaning, its validity, its relationship to African development, neo-colonialism and the global clientelistic structure for continuous dependency, as well as political clientelism importance to African development; by reconstructing the ontological notion of development to the Third World nations as envelopment- overt control of the progress of Third World nations by Global West and by suggesting a possible alternative for a sustainable development